2010
DOI: 10.1016/j.trstmh.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neurotoxoplasmosis characteristics on real-time PCR sensitivity among AIDS patients in Brazil

Abstract: Cerebral toxoplasmosis among individuals with AIDS may be difficult to diagnose and needs to be differentiated from other neurological diseases. A validation study was performed on real-time PCR for detecting the B1 gene of Toxoplasma gondii in the blood and cerebrospinal fluid (CSF) of AIDS patients with cerebral toxoplasmosis. The study included 135 AIDS patients divided into two groups: Group I comprised 85 patients with neurotoxoplasmosis; and Group II comprised 50 patients with non-toxoplasmic neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
3
29
0
3
Order By: Relevance
“…These high sensitivities could indeed be in agreement with the higher virulence of parasite genotypes circulating in South America, but technical pitfalls could also explain such high rates. Indeed, a more recent study did not confirm these data, since those authors found only 29/82 (35%) and 1/85 positive CSF and blood samples, respectively (63).…”
Section: Diagnosis Of Toxoplasmosis In Immunocompromised Patientsmentioning
confidence: 88%
“…These high sensitivities could indeed be in agreement with the higher virulence of parasite genotypes circulating in South America, but technical pitfalls could also explain such high rates. Indeed, a more recent study did not confirm these data, since those authors found only 29/82 (35%) and 1/85 positive CSF and blood samples, respectively (63).…”
Section: Diagnosis Of Toxoplasmosis In Immunocompromised Patientsmentioning
confidence: 88%
“…Molecular methods are particularly appropriate for AIDS patients since these methods are not affected by immunological status and are rapid, sensitive and specific (Colombo, Vidal et al 2005; Pereira-Chioccola, Vidal et al 2009). PCR using CSF has been reported to have a high specificity of 96 to 100% (Pereira-Chioccola, Vidal et al 2009; Correia, Melo et al 2010). However collection of CSF is invasion and may be inappropriate for patients with extensive cerebral lesions with extensive edema.…”
Section: Toxoplasmosis: Clinical Aspectsmentioning
confidence: 99%
“…However collection of CSF is invasion and may be inappropriate for patients with extensive cerebral lesions with extensive edema. Reports on the utility of PCR using peripheral blood samples for diagnosing cerebral toxoplasmosis have been variable (Correia, Melo et al 2010). …”
Section: Toxoplasmosis: Clinical Aspectsmentioning
confidence: 99%
“…For example, IgG titers in AIDS patients are often low and frequently below the sensitivity of detection. Diagnosis based on other biomarkers or PCR based molecular diagnostic techniques are being sought for these patients (26,27).…”
mentioning
confidence: 99%